2014
DOI: 10.1007/s00359-014-0956-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational themes of peripheral processing in the auditory pathway of insects

Abstract: Hearing in insects serves to gain information in the context of mate finding, predator avoidance or host localization. For these goals, the auditory pathways of insects represent the computational substrate for object recognition and localization. Before these higher level computations can be executed in more central parts of the nervous system, the signals need to be preprocessed in the auditory periphery. Here, we review peripheral preprocessing along four computational themes rather than discussing specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Mechanical and non-neural mechanisms of the moth ear contribute to filtering and amplification of the signal. The broadly tuned receptor diverges the signal onto many interneurons providing feature extraction as found in other insects (Hildebrandt et al, 2015). Since the informative signal is a change in the temporal pattern of the bat call, one A cell diverging on ascending interneurons can decode a search from an attack bat call.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical and non-neural mechanisms of the moth ear contribute to filtering and amplification of the signal. The broadly tuned receptor diverges the signal onto many interneurons providing feature extraction as found in other insects (Hildebrandt et al, 2015). Since the informative signal is a change in the temporal pattern of the bat call, one A cell diverging on ascending interneurons can decode a search from an attack bat call.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, further sound sources such as abiotic (Brumm and Slabbekoorn, 2005;Reichert and Ronacher, 2015) or even anthropogenic noise (Lampe et al, 2012(Lampe et al, , 2014Schmidt et al, 2014) may impede signal representation and recognition. Crickets, bushcrickets and grasshoppers are known to employ several processing tools to reduce the detrimental effects of masking and noise (Einhäupl et al, 2011;Schmidt and Römer, 2011;Neuhofer and Ronacher, 2012;Hildebrandt et al, 2015), most prominently by forward masking, selective attention, formation of acoustic hemispheres and stream segregation (Pollack, 1986;Schul and Sheridan, 2006;Triblehorn and Schul, 2009;Schmidt and Römer, 2011). Our experiments support the observations from former studies (Pollack, 1986;Doherty, 1985), which demonstrated that female crickets are able to choose between two patterns and express a clear phonotactic preference irrespective of simultaneous or alternating stimulus situation or intensity differences (Figs 2, 3 and 4).…”
Section: Discussion Signal Representation and Cues For Decision Makingmentioning
confidence: 99%
“…This process represents an on-off mechanism with similarity to a positive half-wave rectifier response with a consequent capacitive charging effect. The cellular membrane of the mechanoreceptor cells can be seen as a small capacitor which charges every time strain increases and discharges when it decreases [18,19]. Auditory mechanoreceptor cells possess synaptic contacts with auditory neurons.…”
Section: Background Biology -The Moth Hearing Systemmentioning
confidence: 99%